2020
DOI: 10.3389/fninf.2020.563669
|View full text |Cite
|
Sign up to set email alerts
|

NeuroRA: A Python Toolbox of Representational Analysis From Multi-Modal Neural Data

Abstract: In studies of cognitive neuroscience, multivariate pattern analysis (MVPA) is widely used as it offers richer information than traditional univariate analysis. Representational similarity analysis (RSA), as one method of MVPA, has become an effective decoding method based on neural data by calculating the similarity between different representations in the brain under different conditions. Moreover, RSA is suitable for researchers to compare data from different modalities and even bridge data from different sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Specifically, we calculated RDM with codes from Neurora (Z. Lu&Ku, 2020b), and then extracted the corresponding neural pattern dissimilarity value from it.(Z. Lu & Ku, 2020b).…”
Section: Figure * Eeg -Tpds and Stpdsmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, we calculated RDM with codes from Neurora (Z. Lu&Ku, 2020b), and then extracted the corresponding neural pattern dissimilarity value from it.(Z. Lu & Ku, 2020b).…”
Section: Figure * Eeg -Tpds and Stpdsmentioning
confidence: 99%
“…We do statistics on neural pattern dissimilarity(NPDS), which calculate pair t-test at each time point and draws a heat map, and the area of the picture framed means significant difference(Z. Lu&Ku, 2020b).(Z. Lu & Ku, 2020b)。 It can be found that in the case of the whole brain, in the middle and late stage, there are significant differences around 0.4s and 0.6s.. This is consistent with the extraction of semantic memory in time, which shows that there are differences in the extraction of this part: STPDS(spaced -once) > STPDS(massed -once).…”
Section: Figure Neural Pattern Dissimilaritymentioning
confidence: 99%
See 3 more Smart Citations